KERAGAMAN IKTIOFAUNA MUARA SUNGAI CIMANUK, INDRAMAYU, JAWA BARAT [Ichthyofaunal Diversity of Cimanuk Estuary, Indramayu, West Java] - Tampubolon, Prawira ARP; Ernawati, Yunizar; Rahardjo, M.F. (BERITA BIOLOGI, 2018)
Cimanuk river, which the estuary formed a delta, is a habitat for many fishes that occupied the water in northern coast of Ja va. The estuary is essential for supporting the fish life cycle. The aim of this study was to asscess the diversity of ichthyo fauna in Cima nuk River estuary. The fishes were collected in three months from July to September 2013 at three locations: Pagirikan, Pabean Ilir and Song. Total fish collected were 1,826 individuals, consisted of 103 species from 41 families and 14 orders. Most of them were from Family Ambassidae,Leiognathidae, Scianidae, Gobiidae, and Ariidae.